Challenges and Strategies in Managing Disruptive Behaviours: Insights from Vietnamese Novice EFL Teachers - Anh Thuc Nguyen; Anh Hoang Thi Tran (Vietnam Journal of Education)
Classroom management is crucial in fostering positive interactions and minimising disruptions to support student learning. However, it is common for novice teachers to face significant challenges in managing disruptive behaviours due to limited training and experience, impacting their teaching effectiveness and job satisfaction. In Vietnam, these challenges are heightened by the new competency-based curricula and students' limited opportunities to use English outside the classroom, which can reduce learner engagement and increase disruptive behaviours. This study explores the perceptions and strategies of Vietnamese novice EFL teachers in managing disruptive behaviours in secondary school classrooms. Using a qualitative design, data were collected from 14 novice teachers in secondary schools across Vietnam through reflective journals and semi-structured interviews. The findings indicate that novice EFL teachers frequently encounter disruptive behaviours, such as lack of concentration, chatting, incomplete homework, and off-task activities, which can hinder their teaching effectiveness. Additionally, the surveyed teachers primarily relied on teacher-centred strategies to maintain control, occasionally adopting student-centred approaches and, in some cases, passive strategies. The findings suggest some implications for enhancing classroom management training to combine theoretical and practical application, while also increasing support from experienced teachers and school administrators. Such support could equip novice teachers with the tools necessary for effective classroom management in EFL settings.